Testing Trade-off and Pecking Order Theories of Capital Structure: Evidence and Arguments - Rahman, Md Takibur (International Journal of Economics and Financial Issues, 2019)
Empirical studies suggests that banks’ capital structure is time invariant and bank-specific. Unobserved time invariant bank-specific effects are important in explaining the financial decision of the banks regarding capital structure. Two theories of finance explaining the target capital structure decisions are tested based on bank specific variables using traditional and advanced panel data econometric models. The study used twenty-seven listed commercial banks in Bangladesh over a period of 2009-2013. The results suggest that profitability, tangibility, liquidity, dividend payment and growth rate have statistically significant effects on capital structure. Five bank specific variables out of the seven confirm the trade-off theory and remaining two confirm pecking order theory. The implication of this study is that the bank specific determinants of capital structure are same as in the finance theory, suggesting that the finance managers of the sample banks may consider these determinants as a benchmark in capital structure decision. Keywords: Leverage, Trade-off, Pecking order, Bank, Capital structure. JEL Classifications: C5, C58, G11 DOI: https://doi.org/10.32479/ijefi.8514